Bad mormon eaudiobook - Gay, Heather (Simon & Schuster Audio, 2023)
INSTANT NEW YORK TIMES BESTSELLER Named one of Entertainment Tonight 's Best Celebrity Memoirs of 2023 As seen in The New York Times , People , The Cut , Vulture , The Daily Beast , Today , Bustle , Us Weekly , Life & Style , and Interview "No stone goes unturned" ( People ) in this memoir about The Real Housewives of Salt Lake City star Heather Gay's departure from the Mormon Church, and her unforeseen success in business, television, and single motherhood. Straight off the slopes and into the spotlight, Heather Gay is famous for speaking the gospel truth. Whether as a businesswoman, mother, or television personality, she is unafraid to blaze a new trail, even if it means losing family, friends, and her community. Born and bred to be devout, Heather based her life around her faith. She attended Brigham Young University, served a mission in France, and married into Mormon royalty in the temple. But her life as a good Mormon abruptly ended when she lost the marriage and faith that she had once believed would last forever. With writing that is beautiful, sad, funny, and true, Heather recounts the difficult discovery of the darkness and damage that often exists behind a picture-perfect life, while examining the nuanced relationship between duty to self and duty to God. "An eye-opening firsthand account of religious indoctrination told with candor and sincerity" ( Interview magazine), Bad Mormon is an unfiltered look at the religion that broke her heart.